A novel study on mechanically alloyed nanocrystalline Ti-6Al-4V alloy fabricated by spark plasma sintering. (15th March 2021) - Ali, Showkat; Karunanithi, R.; Prashanth, M.; Sivasankaran, S.
ABSTRACT: The aim of this research work was to synthesize Ti-6Al-4V nanocrystalline alloy by mechanical alloying (MA) method with different milling times, and consolidate the powders by spark plasma sintering (SPS). The variation of structural parameters with the function of milling time was explored using several models based on x-ray diffraction (XRD) results. The XRD results revealed the formation of Ti(Al) and Ti(Al, V) coherent phases due to solid solution attainment eventually the crystalline size was decreased drastically from 90 nm (0 hr) to 4.4 nm (120 h) obtained from uniform stress deformation model (USDM). The powder surface morphology using HRSEM, physical properties ofsynthesised powders, and powder flow characteristics were investigated. The TEM and HRTEM analyses on the Ti-6Al-4V-120h sample was also examined. Mechanical behaviour and EBSD analyses of bulk samples were also explained and reported. The results of the Ti-6Al-4V-120h bulk sample after SPS exhibited high mechanical properties.